2019
DOI: 10.1038/s41598-019-44183-6
|View full text |Cite
|
Sign up to set email alerts
|

The cytoskeletal crosslinking protein MACF1 is dispensable for thrombus formation and hemostasis

Abstract: Coordinated reorganization of cytoskeletal structures is critical for key aspects of platelet physiology. While several studies have addressed the role of microtubules and filamentous actin in platelet production and function, the significance of their crosstalk in these processes has been poorly investigated. The microtubule-actin cross-linking factor 1 (MACF1; synonym: Actin cross-linking factor 7, ACF7) is a member of the spectraplakin family, and one of the few proteins expressed in platelets, which posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The cytoskeleton is a complex network of filamentous proteins, including semiflexible actin filaments and rigid microtubules [1][2][3] . Numerous crosslinking proteins that can link actin to actin [4][5][6][7] , microtubules to microtubules [8][9][10] , and actin to microtubules [11][12][13][14][15] enable the cytoskeleton to adopt diverse architectures and stiffnesses to drive key processes such as cell motility, meiosis and apoptosis 10,[16][17][18] . These varying structural and rheological properties, in turn, directly impact the intracellular transport of vesicles and macromolecules traversing the cytoplasm 14,15,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…The cytoskeleton is a complex network of filamentous proteins, including semiflexible actin filaments and rigid microtubules [1][2][3] . Numerous crosslinking proteins that can link actin to actin [4][5][6][7] , microtubules to microtubules [8][9][10] , and actin to microtubules [11][12][13][14][15] enable the cytoskeleton to adopt diverse architectures and stiffnesses to drive key processes such as cell motility, meiosis and apoptosis 10,[16][17][18] . These varying structural and rheological properties, in turn, directly impact the intracellular transport of vesicles and macromolecules traversing the cytoplasm 14,15,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study investigating the role of ACF7 in platelets using Macf1 fl to conditionally knockout the gene also revealed that ACF7 was not required for proper function in certain contexts. These findings are relevant because, similar to hair cells, platelets have a robust cytoskeletal structure that is required for the cell to survive and function properly ( Schurr et al, 2019 ). This suggests that both hair cells and platelets have possible redundancy of the cytoskeleton proteins to safeguard their precise structure that is essential for their function.…”
Section: Discussionmentioning
confidence: 99%
“…Heparinized whole blood was diluted in a ratio of 2:1 in Tyrode’s-Hepes buffer containing Ca 2+ ( 43 ). Whole blood or mixed platelet count adjusted blood (5 × 10 5 platelets/μl) was incubated with an anti-GPIX antibody derivate conjugated with DyLight 488 (0.2 μg/ml) at 37°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%